Effect of Oct3 Genetic Polymorphism on the Response of Metformin in Type 2 Diabetes Mellitus: Narrative Review - Swathi Swaroopa Borra; Bhavya Chebrolu; Poojitha T; Sujin Bright F J; Sadagoban GK; Arun Kanniyappan Parthasarathy (Journal of Global Pharma Technology, 2021)
Context: Metformin, the first line therapy of Type 2 Diabetes Mellitus is known to be transported by OCT3 (Organic Cation Transporter 3). Polymorphisms in this gene may lead to interindividual differences in the response to metformin. Objective: This study aims to compile and summarise the effect of OCT3 polymorphism on effect of metformin. Methods: PubMed/MEDLINE, ResearchGate, Google Scholar, Cochrane Library and Scopus were used for literature review. Cmax (Maximum concentration), Tmax (Time to reach maximum concentration), AUC (Area under the curve) and Kel (Elimination rate constant) were used to assess pharmacokinetics and HbA1c (Hemoglobin A1c), blood glucose levels for pharmacodynamics. Results: Data extraction showed that 19 OCT3 polymorphisms were analyzed in various ethnic communities with the plurality of Asians. The results of these genotype alleles were found to be favorable (9), negative (3) and have no impact (7) on the response of metformin. A positive effect on metformin response was expressed as higher Cmax (Maximum concentration), AUC (Area under the curve), lower Kel (Elimination rate constant) or reduced HbA1c (Hemoglobin A1c), FBG (Fasting blood glucose). Conclusion: Influence of OCT3 polymorphisms on metformin responses were unique to the population. This recommends new research requirement on association between OCT3 polymorphism and Metformin.